Pemberdayaan Wanita melalui Pelatihan Pembuatan Healthy Pastry dan Bakery Product di LSM Perempuan Binangkit Bandung - Chandra, Teddy; Prabowo, Susilo Dwi; Roesfian, Erfin; Wicaksono, Aditya; Arifin, Djauhar; Utomo, Bambang Sapto; Maulina, Lien; Susanto, Heri; Sufianti, Arti; Asmara, Andi; Hafizh, Fauzhiyah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Women Empowerment Through Healthy Pastry & Bakery Product Making Training at LSM Perempuan Binangkit Bandung is a community service program implemented by lecturers and students of the Pastry Processing Art Study Program, NHI Bandung Tourism Polytechnic. The purpose of this program is not only to improve the cooking skills and knowledge of the participants in order to improve the household economy, but it is also expected to be an alternative solution to solving the problem of increasing the risk of catastrophic diseases caused by inappropriate food intake and not in accordance with the recommendations of health institutions. This program is implemented using the cooking demonstration and hands-on practice methods. After the implementation of the healthy pastry & bakery product making training program, it can be concluded that the training participants became more skilled and knowledgeable in the process of making healthy pastry & bakery products which are expected to reduce the risk of catastrophic diseases.